A biaxially stretched polyolefin film and preparation method thereof

By introducing cycloolefin polymers into the biaxially stretched polypropylene film and using synchronous bidirectional stretching technology and anti-aging agents, the problem of insufficient heat resistance and anti-aging ability of BOPP film in high-temperature environments is solved, and higher dielectric strength and dimensional stability are achieved, and it is suitable for high-performance capacitors and other equipment.

CN118994790BActive Publication Date: 2025-02-28QUANZHOU JIADELI ELECTRONIC MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411479794.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-28
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Biaxially stretched polypropylene film (BOPP film) exhibits poor heat resistance and weak aging resistance under high temperature environments, resulting in a decline in its performance in applications in electronics, electrical and new energy vehicles.

Method used

A biaxially stretched polyolefin film was prepared by blending 1~8 wt% cycloolefin polymer (COC) with 91~97 wt% partially crystallized propylene homopolymer, and the heat resistance and anti-aging properties of the film were improved by synchronous bidirectional stretching technology and the addition of anti-aging agents.

Benefits of technology

It improves the dielectric strength and dimensional stability of the polyolefin film at high temperatures, enhances its anti-aging ability for long-term working, alleviates the performance deterioration caused by environmental heating, and is suitable for electronic and electrical equipment such as high-performance capacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a biaxially stretched polyolefin film and a preparation method thereof, and relates to the technical field of polyolefin films. The biaxially stretched polyolefin film is prepared from the following components by mass percentage: 1-8wt% of a cycloolefin polymer with a glass transition temperature of 120-170°C, 91-97wt% of a partially crystallized propylene homopolymer with a crystal melting temperature of 150-170°C, and 0-4wt% of an additive. The cycloolefin polymer content of 1-8wt% can significantly improve the heat resistance, dielectric properties and dimensional stability of the film material without excessively affecting the processing performance and cost. The 91-97wt% high-purity propylene homopolymer with a narrow molecular weight distribution ensures the excellent mechanical and electrical properties of the film material. The prepared polyolefin film has higher crystal melting point and glass transition temperature while maintaining good processing performance and economy, and has higher high-temperature dielectric strength, more excellent heat resistance and dimensional stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyolefin films, and in particular to a biaxially stretched polyolefin film and a preparation method thereof. Background Art

[0002] Biaxially oriented polyolefin film, especially biaxially oriented polypropylene film (BOPP film), has become one of the preferred materials for capacitor insulation due to its excellent electrical and mechanical properties. BOPP film for capacitors is a specially designed and manufactured high-performance film, and its performance directly affects the efficiency and reliability of modern electronic and electrical equipment.

[0003] BOPP film for capacitors needs to meet strict performance requirements, including extremely high dielectric strength (breakdown strength is usually required to be greater than 500 V / μm), extremely low dielectric loss (dielectric loss factor is usually less than 0.0002), excellent self-healing performance, good heat resistance and dimensional stability, high purity (extremely low impurity content) and excellent flatness and uniformity. In addition, this film material is also required to have a high dielectric constant (typical value is about 2.2), high volume resistivity (greater than 1016Ω·cm) and good heat resistance (usually required to be able to work stably for a long time at 85℃ or higher).

[0004] The manufacturing process of BOPP film for capacitors is similar to that of ordinary BOPP film, but it has more stringent requirements in terms of raw material selection, production environment control and post-processing. Usually, high-purity, narrow molecular weight distribution propylene homopolymer resin is used, and it is produced in a clean environment with strict control of impurities and defects. At the same time, precise stretching and heat setting processes are used to ensure the uniformity and dimensional stability of the film. In some cases, special surface treatment is also required to improve the metallization effect.

[0005] BOPP film is mainly used as a dielectric material and metallized substrate in capacitors. It can produce capacitors with small size and large capacity, high reliability, low loss and good pulse characteristics, suitable for high frequency and high current applications. When local breakdown occurs, the metallized layer can quickly vaporize, isolate the defective area, and ensure that the capacitor continues to work. This excellent self-healing performance greatly improves the service life of the capacitor.

[0006] The current application problem that BOPP capacitor film urgently needs to be solved is its poor high-temperature stability. In the fields of electronics, electrical and new energy vehicles, the capacitor itself generates heat due to frequent charging and discharging, and the heat generation and heat transfer of the surrounding motor group is even more serious. The heating and temperature rise of the application environment causes the performance of BOPP capacitor film to decline sharply, which not only includes an increase in thermal shrinkage (decreased dimensional stability), but also brings a significant decrease in breakdown strength, resulting in reduced reliability of the capacitor and increased failure rate. In addition, the increased aging of the film caused by the increase in environmental temperature is also an important reason for its serious performance loss and reduced lifespan.

[0007] In order to improve the performance of BOPP film, researchers introduced cycloolefin polymer (COC) into propylene homopolymer. COC has the characteristics of high transparency, low density, low hygroscopicity, excellent chemical resistance, high heat deformation temperature, low dielectric constant and dielectric loss. These characteristics enable COC to significantly improve the heat resistance, dielectric properties and dimensional stability of film materials, and are expected to solve the problem of insufficient performance of traditional BOPP film in high temperature environment.

[0008] Chinese patent document CN110546190B discloses a biaxially stretched polyolefin film comprising the following components: (a) 10 to 45 wt % of a cycloolefin polymer having a glass transition temperature between 120 and 170°C, and (b) 90 to 55 wt % of a partially crystallized α-olefin polymer having a crystalline melting temperature between 150 and 170°C, wherein the glass transition temperature of component (a) is less than or equal to the crystalline melting temperature of component (b), and the polyolefin film has a shrinkage of less than or equal to 2% measured according to DIN ISO 11501 after 5 minutes at 130°C.

[0009] However, the preparation of biaxially stretched films by blending COC with propylene homopolymer still faces some challenges, mainly in two aspects: first, based on the mismatch of the processing windows of the two materials, high COC content will significantly increase the difficulty of film processing, resulting in the difficulty of effectively controlling the uniformity and stability of the film stretching process, and even affecting the performance; second, although the addition of COC can improve the high temperature resistance of the film, there is still huge room for development in other functional enhancements. Therefore, the development of a new biaxially stretched polyolefin film that can give full play to the advantages of COC while taking into account processing performance and economy is the focus and difficulty of current research. Summary of the invention

[0010] In order to address the deficiencies in the prior art and the poor high temperature resistance and aging resistance of BOPP film, the purpose of the present invention is to provide a biaxially stretched polyolefin film and a preparation method thereof. The prepared polyolefin film has higher crystal melting point and glass transition temperature while maintaining good processing performance and economy. At high temperatures, the film has higher dielectric strength and dimensional stability, outstanding aging resistance after long-term operation, can effectively alleviate the degradation of film performance caused by environmental warming, improve high temperature stability, and is particularly suitable for use in electronic and electrical equipment such as high-performance capacitors.

[0011] In order to achieve the above object, the present invention adopts the following technical solution:

[0012] A biaxially stretched polyolefin film is made of the following components by mass percentage: 1-8wt% of a cycloolefin polymer with a glass transition temperature of 120-170°C, 91-97wt% of a partially crystallized propylene homopolymer with a crystal melting temperature of 150-170°C, and 0-4wt% of an additive.

[0013] Preferably, the glass transition temperature of the cycloolefin copolymer is between 130 and 170°C.

[0014] Preferably, the cycloolefin copolymer has a melt flow index between 0.3 and 4 g / 10 min, and the melt flow index is measured at 230° C. and a load of 2.16 kg.

[0015] Preferably, the cycloolefin polymer is obtained by copolymerizing at least one cycloolefin of formula I with at least one α-olefin of formula II in a ring-preserving manner.

[0016] .

[0017] Where n is 0 or 1, m is 0 or a positive integer, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 independently represent hydrogen, halogen, alkyl, alkoxy, cycloalkyl, aryl or aralkyl, R 7 , R 8 , R 9 , R 10 , R 11 , R 12 , R 13 , R 14 , R 15 , R 16 are independently hydrogen or alkyl, R 17 , R 18 , R 19 , R20 are independently hydrogen, halogen or alkyl,

[0018] Or, where R 17 and R 19 Together with the carbon atoms to which they are attached, they form a saturated or unsaturated ring or multiple saturated or unsaturated rings,

[0019]

[0020] Where R 21 and R 22 Independently of each other represent hydrogen or alkyl.

[0021] Preferably, the biaxially stretched polyolefin film is a single-layer film or a multi-layer film, and at least one film in the multi-layer film is the biaxially stretched polyolefin film.

[0022] Preferably, the biaxially stretched polyolefin film has a thickness measured according to DIN 53370 between 1 and 10 μm.

[0023] Preferably, the additive is one or more of a processing aid, a plasticizer, a UV stabilizer, a matting agent, a preservative, a biocide, an antioxidant, an antistatic agent, a fire retardant, a reinforcing agent, a filler, a pigment, and a fuel.

[0024] Preferably, the additive is an anti-aging agent, the mass percentage of which is 0.1-4wt%, and the preparation method comprises the following steps:

[0025] (1) 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and hydroxyethyl methacrylate are added to chloroform, and then concentrated sulfuric acid is slowly added dropwise. The temperature is raised under a nitrogen atmosphere to react. The product is poured into ice water to quench, extracted with chloroform, and the organic phase is dried with anhydrous sodium sulfate. The solvent is removed by reduced pressure distillation to obtain an intermediate;

[0026] Friedel-Crafts alkylation reaction of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole with hydroxyethyl methacrylate: Concentrated sulfuric acid protonates the hydroxyl group of hydroxyethyl methacrylate to form a good leaving group. Subsequently, the hydroxyl group leaves to form a stable carbon cation intermediate. This carbon cation acts as an electrophilic reagent to attack the carbon atom ortho to the phenolic hydroxyl group in the 2-(2'-hydroxy-5'-methylphenyl)benzotriazole molecule (this position has a higher electron density due to the directional effect of the phenolic hydroxyl group). The reaction product retains the phenolic hydroxyl group and benzotriazole structure of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, and at the same time introduces an acrylate group at the ortho position.

[0027] Preferably, in step (1), the usage ratio of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hydroxyethyl methacrylate and concentrated sulfuric acid is 10-20:12-30 g:0.1-0.5 mL; and the concentration of concentrated sulfuric acid is 95-98 wt %.

[0028] Preferably, in step (1), the temperature is raised to 50-70° C. for 2-4 hours.

[0029] (2) dissolving the intermediate in anhydrous ethyl acetate, adding IPDI dropwise under a nitrogen atmosphere, and then adding DBTDL, stirring the reaction, and distilling the product under reduced pressure to remove the solvent to obtain a modifier;

[0030] Addition reaction of the intermediate with isophorone diisocyanate (IPDI): The dibutyltin dilaurate (DBTDL) catalyst coordinates with the -NCO group of IPDI to increase its electrophilicity. Subsequently, the -OH on the intermediate undergoes nucleophilic addition to the activated -NCO. Finally, a carbamate bond (-NHCOO-) is formed through proton transfer. The reaction product contains the core structure of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, the newly formed carbamate link, and the remaining -NCO group from IPDI, which is ready for the subsequent reaction with nano zinc oxide.

[0031] Preferably, in step (2), the usage ratio of the intermediate, IPDI and DBTDL is 10-15 g: 10.5-18 g: 0.01-0.75 g.

[0032] Preferably, in step (2), the stirring reaction condition is 70-77° C. for 3-6 hours.

[0033] (3) Dispersing nano zinc oxide in xylene, ultrasonically treating, then dropwise adding a modifier, stirring to react under a nitrogen atmosphere, centrifuging, washing with alcohol, and drying the product to obtain the anti-aging agent.

[0034] Surface modification reaction of modifier and nano zinc oxide: -NCO group in the modifier undergoes nucleophilic addition reaction with -OH group on the surface of zinc oxide to form carbamate bond (-NHCOO-), thereby covalently connecting 2-(2'-hydroxy-5'-methylphenyl)benzotriazole derivative to the surface of zinc oxide. The key to this step is to ensure that the modifier is evenly covered on the surface of zinc oxide to form a stable chemical bond connection. The final product is nano zinc oxide particles whose surface is modified by 2-(2'-hydroxy-5'-methylphenyl)benzotriazole derivative, which combines the ultraviolet absorption ability of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and the reflection and scattering properties of nano zinc oxide to form a highly efficient composite anti-aging agent.

[0035] Preferably, in step (3), the dosage ratio of nano zinc oxide, xylene and modifier is 10-20 g: 100-200 mL: 5-10 g.

[0036] Preferably, in step (3), the ultrasonic treatment is performed for 20 to 40 minutes; and the stirring reaction conditions are 90 to 100° C. and the reaction is performed for 6 to 12 hours.

[0037] Preferably, in step (3), the particle size of nano zinc oxide is 10-100 nm.

[0038] Preferably, the additive is an anti-aging agent, and the mass percentage is 0.1-4wt%, which can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%; its structural formula is as follows:

[0039]

[0040] In the formula, Refers to nano zinc oxide.

[0041] The present invention also claims the use of the biaxially stretched polyolefin film in capacitors.

[0042] The present invention also claims protection for a method for preparing the biaxially stretched polyolefin film, which is a biaxial stretching technology targeted at the PP / COC blending system, comprising the following steps: putting a propylene homopolymer, a cycloolefin polymer and an additive into a mixing device and mixing them evenly, feeding them into an extruder, and the extruder plasticizes the mixed melt through seven stages of heating and stabilizing pressure to ensure that the raw materials are fully plasticized and blended, the melt is filtered through two stages, metered and extruded to a chilled roller, and the chilled roller cools the melt to obtain a thick sheet to be stretched; heating in a preheating zone of a synchronous stretching oven, and transversely stretching it into a film at a higher temperature to ensure that both the rigid COC chain and the flexible PP chain have high molecular chain mobility; and winding up after trimming, thickness measurement and corona treatment to obtain the biaxially stretched polyolefin film.

[0043] Preferably, the temperatures of the seven sections of the extruder are respectively 235-245°C for the feeding section I-II, 250-265°C for the melting section III-V, and 250-260°C for the homogenizing section VI-VII; the metering pump speed is 25-35r / min, the extruder speed is 25-35r / min, the chilled roller temperature is 75-85°C, and the chilled roller speed is 40-50r / min; the preheating zone temperature is 155±2°C, 158±2°C, 161±2°C, and 163±2°C; the corona treatment power is 19±1Wmin / m 2 ;Film winding tension 30±3N / m.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The present invention provides a biaxially stretched polyolefin film that gives full play to the advantages of cycloolefin polymer (COC) and propylene homopolymer. The COC content of 1-8wt% can significantly improve the heat resistance, dielectric properties and dimensional stability of the film material without excessively affecting the processing performance and cost. The high-purity, narrow molecular weight distribution propylene homopolymer of more than 91wt% ensures the excellent mechanical and electrical properties of the film material. This formula design allows the biaxially stretched polyolefin film of the present invention to have a higher crystal melting point and glass transition temperature while maintaining good processing performance and economy. At high temperatures, the film has higher dielectric strength and dimensional stability, and has outstanding anti-aging ability for long-term operation. It can effectively alleviate the degradation of film performance caused by environmental warming, and is particularly suitable for use in electronic and electrical equipment such as high-performance capacitors.

[0046] (2) The present invention provides a synchronous biaxial stretching technology that matches the PP / COC blending system. The notable features of this technology are that a more finely differentiated extrusion section design and a higher melt extrusion temperature are used to ensure that the two materials are fully blended and plasticized, and a higher stretching temperature is used to ensure that the COC molecular chain and the PP molecular chain achieve a higher molecular chain mobility that matches. This process can produce PP / COC blended films that are similar in thickness to pure PP films (~2.4μm) and have a higher crystal melting point and a higher glass transition temperature.

[0047] (3) The present invention provides a method for preparing an anti-aging agent. First, concentrated sulfuric acid is used as a catalyst to combine 2-(2'-hydroxy-5'-methylphenyl)benzotriazole with hydroxyethyl methacrylate through a Friedel-Crafts alkylation reaction, and an intermediate with UV absorption capacity is efficiently obtained under mild conditions. Subsequently, the intermediate is modified by isophorone diisocyanate (IPDI), and the phenolic hydroxyl group (-OH) on the intermediate undergoes a nucleophilic addition reaction with the activated isocyanate group (-NCO) in IPDI, which not only enhances the compatibility of the modifier with the polymer matrix, but also provides an active group for the next step of combining with nano zinc oxide. Finally, the modifier is compounded with nano zinc oxide, and the remaining isocyanate group (-NCO) in the modifier undergoes a nucleophilic addition reaction with the hydroxyl group (-OH) on the surface of the nano zinc oxide to form a stable chemical bond, thereby improving the overall performance of the anti-aging agent and ensuring the uniform dispersion of the nanoparticles in the polymer matrix. Finally, a composite additive that can be tightly combined with the polymer matrix and has excellent anti-aging performance is obtained.

[0048] (4) The present invention provides an anti-aging agent, wherein 2-(2'-hydroxy-5'-methylphenyl)benzotriazole is used as an organic UV absorber, which can effectively absorb ultraviolet rays of 290-350nm and convert them into heat energy dissipation. At the same time, nano zinc oxide is used as an inorganic UV shielding agent, which can not only absorb ultraviolet rays, but also scatter UV light through its high refractive index to form a physical barrier. The synergistic effect of these two components significantly improves the overall performance of the anti-aging agent and achieves wide-spectrum and high-efficiency UV protection. Through IPDI modification, the compatibility of the anti-aging agent with the polymer matrix is ​​enhanced, the problem of additive migration and precipitation is avoided, and the long-term stability of the film material is improved. The nano-scale particle size ensures the uniform dispersion of the additive in the film and does not affect the transparency and mechanical properties of the film. In addition, the unsaturated carbon-carbon double bonds introduced by hydroxyethyl methacrylate can participate in polymerization during the melt blending process with PP resin and produce chemical reactions with the PP matrix, which not only enhances the interaction between nano zinc oxide and the matrix, but also plays a micro-crosslinking effect, thereby improving the durability of the anti-aging agent and improving the mechanical strength of the polyolefin film. In summary, the antioxidant of the present invention achieves excellent UV protection effect, good compatibility and long-term stability through multiple mechanisms and carefully designed molecular structures, while improving the overall performance of the film material and significantly improving the weather resistance and service life of the biaxially stretched polyolefin film. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show schematic diagrams of certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0050] Figure 1 The DSC melting curves (a) and dynamic thermomechanical analysis spectra (b) of the polyolefin films prepared in Example 1 and Comparative Example 3; Comparative Example 4 and Comparative Example 5 are shown. DETAILED DESCRIPTION

[0051] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0052] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0053] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.

[0054] The propylene homopolymer is high-purity PP (capacitor grade), purchased from Borealis AG, model BorcleanHC300BF, Borclean HC310BF; in addition, Singapore FS3030, FS3031, Korea's HPT-1, HPT-V can also be selected;

[0055] Cyclic olefin polymer was purchased from TOPAS Advanced Polymers GmbH, Frankfurt am Main, model TOPAS 6014.

[0056] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0057] (1) Add 10-20 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 12-30 g of hydroxyethyl methacrylate to 100 mL of chloroform, then slowly dropwise add 0.1-0.5 mL of 95-98 wt% concentrated sulfuric acid, heat to 50-70 °C under a nitrogen atmosphere and react for 2-4 h, pour the product into ice water to quench, extract with chloroform, dry the organic phase with anhydrous sodium sulfate, and remove the solvent by reduced pressure distillation to obtain an intermediate;

[0058] (2) Dissolve 10-15 g of the intermediate in 100 mL of anhydrous ethyl acetate, add 10.5-18 g of IPDI dropwise under a nitrogen atmosphere, and then add 0.01-0.75 g of DBTDL. Stir the reaction at 70-77 °C for 3-6 h, and distill the product under reduced pressure to remove the solvent to obtain a modifier.

[0059] (3) dispersing 10-20 g of nano zinc oxide in 100-200 mL of xylene, ultrasonically treating for 20-40 min, then dropwise adding 5-10 g of a modifier, stirring and reacting at 90-100 °C in a nitrogen atmosphere for 6-12 h, centrifuging the product, washing with alcohol, and drying to obtain the anti-aging agent;

[0060] (4) 1~8wt% cycloolefin polymer, 91~97wt% propylene homopolymer and 0~4wt% additive are put into a mixing device and mixed evenly, and then fed into an extruder. The extruder is heated and pressurized in seven stages to plasticize the mixed material into a melt. The temperatures of the seven stages of the extruder are respectively feeding stage I~II 235~245℃, melting stage III~V 250~265℃, homogenizing stage VI~VII 250~260℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25~35r / min, the extruder speed is 25~35r / min, the chilled roller temperature is 75~85℃, and the chilled roller speed is 40~50r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, and 163±2℃; it is rolled up after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained.

[0061] The present invention will be further described below through specific embodiments. Example 1

[0062] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0063] (1) Add 20 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 30 g of hydroxyethyl methacrylate to 100 mL of chloroform, then slowly dropwise add 0.5 mL of 98 wt% concentrated sulfuric acid, heat to 70 °C under a nitrogen atmosphere and react for 2 h, pour the product into ice water to quench, extract with chloroform, dry the organic phase with anhydrous sodium sulfate, and remove the solvent by reduced pressure distillation to obtain an intermediate;

[0064] (2) Dissolve 15 g of the intermediate in 100 mL of anhydrous ethyl acetate, add 18 g of IPDI dropwise under a nitrogen atmosphere, then add 0.75 g of DBTDL, stir and react at 77 °C for 3 h, and distill the product under reduced pressure to remove the solvent to obtain a modifier;

[0065] (3) Dispersing 20 g of nano zinc oxide in 200 mL of xylene, ultrasonically treating for 40 min, then dropwise adding 10 g of a modifier, stirring and reacting at 100 °C in a nitrogen atmosphere for 6 h, centrifuging the product, washing with alcohol, and drying to obtain the anti-aging agent;

[0066] (4) 30g of cycloolefin polymer, 950g of propylene homopolymer (HC300BF) and 20g of anti-aging agent were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Example 2

[0067] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0068] (1) 15 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 21 g of hydroxyethyl methacrylate were added to 100 mL of chloroform, and then 0.3 mL of 98 wt% concentrated sulfuric acid was slowly added dropwise. The temperature was raised to 60 °C under a nitrogen atmosphere and the reaction was carried out for 3 h. The product was poured into ice water for quenching, extracted with chloroform, and the organic phase was dried with anhydrous sodium sulfate. The solvent was removed by reduced pressure distillation to obtain an intermediate;

[0069] (2) Dissolve 12 g of the intermediate in 100 mL of anhydrous ethyl acetate, add 14 g of IPDI dropwise under a nitrogen atmosphere, then add 0.38 g of DBTDL, stir and react at 74 °C for 5 h, and distill the product under reduced pressure to remove the solvent to obtain a modifier;

[0070] (3) Dispersing 15 g of nano zinc oxide in 150 mL of xylene, ultrasonically treating for 30 min, then dropwise adding 8 g of a modifier, stirring and reacting at 95 °C in a nitrogen atmosphere for 9 h, centrifuging the product, washing with alcohol, and drying to obtain the anti-aging agent;

[0071] (4) 30g of cycloolefin polymer, 960g of propylene homopolymer (HC300BF) and 10g of anti-aging agent were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Example 3

[0072] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0073] (1) 10 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 12 g of hydroxyethyl methacrylate were added to 100 mL of chloroform, and then 0.1 mL of 98 wt% concentrated sulfuric acid was slowly added dropwise. The temperature was raised to 50 °C under a nitrogen atmosphere and the reaction was carried out for 4 h. The product was poured into ice water for quenching, extracted with chloroform, and the organic phase was dried with anhydrous sodium sulfate. The solvent was removed by reduced pressure distillation to obtain an intermediate;

[0074] (2) Dissolve 10 g of the intermediate in 100 mL of anhydrous ethyl acetate, add 10.5 g of IPDI dropwise under a nitrogen atmosphere, then add 0.01 g of DBTDL, stir and react at 70 °C for 6 h, and distill the product under reduced pressure to remove the solvent to obtain a modifier;

[0075] (3) Dispersing 10 g of nano zinc oxide in 100 mL of xylene, ultrasonically treating for 20 min, then dropwise adding 5 g of a modifier, stirring and reacting at 90 °C in a nitrogen atmosphere for 12 h, centrifuging the product, washing with alcohol, and drying to obtain the anti-aging agent;

[0076] (4) 20g of cycloolefin polymer, 970g of propylene homopolymer (HC300BF) and 10g of anti-aging agent were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Comparative Example 1

[0077] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0078] (1) Add 20 g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and 30 g of hydroxyethyl methacrylate to 100 mL of chloroform, then slowly dropwise add 0.5 mL of 98 wt% concentrated sulfuric acid, heat to 70 °C under a nitrogen atmosphere and react for 2 h, pour the product into ice water to quench, extract with chloroform, dry the organic phase with anhydrous sodium sulfate, and remove the solvent by reduced pressure distillation to obtain an intermediate;

[0079] (2) Dissolve 15 g of the intermediate in 100 mL of anhydrous ethyl acetate, add 18 g of IPDI dropwise under a nitrogen atmosphere, then add 0.75 g of DBTDL, stir and react at 77 °C for 3 h, and distill the product under reduced pressure to remove the solvent to obtain a modifier;

[0080] (3) 30g of cycloolefin polymer, 950g of propylene homopolymer (HC300BF) and 20g of modifier were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Comparative Example 2

[0081] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0082] 30g of cycloolefin polymer, 950g of propylene homopolymer (HC300BF), and 20g of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenizing stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Comparative Example 3

[0083] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0084] 50g of cycloolefin polymer and 950g of propylene homopolymer (HC300BF) were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Comparative Example 4

[0085] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0086] 350g of cycloolefin polymer and 650g of propylene homopolymer (HC300BF) were put into a mixing device and mixed evenly, and then fed into an extruder. The extruder was plasticized into a mixed melt through seven stages of heating and stabilizing pressure. The seven stages of the extruder temperature were feeding stage I~II 240℃, melting stage III~V 250℃, 260℃, 260℃, homogenization stage VI~VII. 260℃, 255℃; the melt is filtered in two stages and extruded to the chilled roller. The chilled roller cools the melt to obtain a thick sheet to be stretched. The metering pump speed is 25.9r / min, the extruder speed is 30r / min, the chilled roller temperature is 80℃, and the chilled roller speed is 45r / min; it is heated in the preheating zone of the synchronous stretching oven and stretched horizontally into a film. The preheating zone temperature is 155±2℃, 158±2℃, 161±2℃, 163±2℃; it is wound after trimming, thickness measurement, and corona treatment. The corona treatment power is 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained. Comparative Example 5

[0087] A method for preparing a biaxially stretched polyolefin film comprises the following steps:

[0088] 1000g of propylene homopolymer (HC300BF) was put into the mixing equipment and mixed evenly, and then fed into the extruder. The extruder was plasticized into a mixed melt through seven-stage heating and stabilizing pressure. The seven-stage temperatures of the extruder were feeding section I~II 230℃, melting section III~V 250℃, and homogenizing section VI~VII 245℃. The melt was filtered through two stages and extruded to a chilled roller. The chilled roller cooled the melt to obtain a thick sheet to be stretched. The metering pump speed was 25.9r / min, the extruder speed was 30r / min, the chilled roller temperature was 80℃, and the chilled roller speed was 45r / min. After being heated in the preheating zone of the synchronous stretching oven, it was transversely stretched into a film. The preheating zone temperature was 150±2℃, 152±2℃, 155±2℃, and 158±2℃. After trimming, thickness measurement, and corona treatment, it was rolled up. The corona treatment power was 19±1Wmin / m 2 , the film winding tension is 30±3N / m, and the biaxially stretched polyolefin film is obtained.

[0089] The performance of the polyolefin membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested. 2 ) were placed in an ultraviolet lamp aging test box (model UVZN-320) and subjected to ultraviolet accelerated aging test according to the method described in ISO 4892.3 "Plastics laboratory light source exposure method Part 3 Fluorescent ultraviolet lamp". The test conditions are as follows: light source, UVA-320; radiation energy, 0.83W / (m 2 nm); test temperature, 70℃; 4 hours of light exposure, 1 hour of light off, 200 hours of cycle test; before and after aging, the tensile strength, elongation at break and its retention rate were tested with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets". Specific data are shown in Table 1.

[0090] Table 1 Test results of anti-aging properties of polyolefin films

[0091]

[0092] The performance tests of the olefin polymer films prepared in Comparative Examples 3 to 5 were carried out, and the heat shrinkage and breakdown strength were tested with reference to GB / T 13542.2-2021 “Films for electrical insulation Part 2: Test methods”. The specific data are shown in Table 2.

[0093] Table 2 Comparative Examples 3 to 5 Polyolefin Film Performance Test Results

[0094]

[0095] A high temperature step voltage self-healing test (attenuation of capacitor capacitance at 105°C) was performed on Comparative Examples 3 and 5. At 105°C, the maximum withstand voltage of the capacitor of the Comparative Example 3 film was about 150V higher than that of the Comparative Example 5 film. The specific data are shown in Table 3.

[0096] Table 3 High temperature step voltage self-healing test (105℃)

[0097]

[0098] The polyolefin films prepared in Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5 were subjected to a crystalline melting point test, with reference to GB / T 19466.3-2004, with a programmed heating rate of 10 °C / min. For specific data, see Figure 1 Curve a in the figure. Dynamic mechanical analysis (DMA) was performed on Example 1, Comparative Example 3, Comparative Example 4 and Comparative Example 5. The instrument used was DMA Q800 produced by TA Company of the United States. The test mode was tensile mode, the test temperature range was -70~150℃, the heating rate was 3℃ / min, and the amplitude was 10 μm. For specific data, see Figure 1 Curve b in .

[0099] The technical scheme of Example 1 is 3wt% cycloolefin polymer, 95wt% propylene homopolymer, and 2wt% anti-aging agent; the technical scheme of Comparative Example 3 is 5wt% cycloolefin polymer, 95wt% propylene homopolymer, and 0wt% anti-aging agent; the technical scheme of Comparative Example 4 is 35wt% cycloolefin polymer, 65wt% propylene homopolymer, and 0wt% additive (CN110546190B); the technical scheme of Comparative Example 5 is 100wt% propylene homopolymer.

[0100] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A biaxially stretched polyolefin film, characterized in that: The invention is made of the following components in terms of mass percentage: 1-8 wt% of a cycloolefin polymer having a glass transition temperature of 120-170°C, 91-97 wt% of a partially crystallized propylene homopolymer having a crystal melting temperature of 150-170°C, and additives; The additive is an anti-aging agent, the mass percentage is 0.1~4wt%, and the structural formula is as follows: , In the formula, Refers to nano zinc oxide.

2. The biaxially stretched polyolefin film according to claim 1, characterized in that The additive is an anti-aging agent, the mass percentage is 0.1-4wt%, and the preparation method comprises the following steps: (1) 2-(2'-hydroxy-5'-methylphenyl)benzotriazole and hydroxyethyl methacrylate are added to chloroform, and then concentrated sulfuric acid is slowly added dropwise. The temperature is raised under a nitrogen atmosphere to react. The product is poured into ice water to quench, extracted with chloroform, and the organic phase is dried with anhydrous sodium sulfate. The solvent is removed by reduced pressure distillation to obtain an intermediate; (2) dissolving the intermediate in anhydrous ethyl acetate, adding IPDI dropwise under a nitrogen atmosphere, and then adding DBTDL, stirring the reaction, and distilling the product under reduced pressure to remove the solvent to obtain a modifier; (3) Dispersing nano zinc oxide in xylene, ultrasonically treating, then dropwise adding a modifier, stirring to react under a nitrogen atmosphere, centrifuging, washing with alcohol, and drying the product to obtain the anti-aging agent.

3. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (1), the usage ratio of 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, hydroxyethyl methacrylate and concentrated sulfuric acid is 10-20 g:12-30 g:0.1-0.5 mL; and the concentration of concentrated sulfuric acid is 95-98 wt %.

4. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (1), the temperature is raised to 50-70° C. for 2-4 hours.

5. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (2), the usage ratio of the intermediate, IPDI and DBTDL is 10-15 g: 10.5-18 g: 0.01-0.75 g.

6. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (2), the stirring reaction conditions are 70-77° C. for 3-6 hours.

7. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (3), the dosage ratio of nano zinc oxide, xylene and modifier is 10-20 g: 100-200 mL: 5-10 g.

8. A biaxially stretched polyolefin film as claimed in claim 2, characterized in that: In step (3), the ultrasonic treatment is performed for 20 to 40 minutes; and the stirring reaction condition is 90 to 100° C. for 6 to 12 hours.

9. A method for preparing a biaxially stretched polyolefin film according to any one of claims 1 to 8, characterized in that: The invention is a biaxial stretching technology targeted at PP / COC blending system, comprising the following steps: putting propylene homopolymer, cycloolefin polymer and additives into a mixing device and mixing them evenly, feeding them into an extruder, and the extruder plasticizes the mixed melt through seven-stage heating and stabilizing pressure to ensure that the raw materials are fully plasticized and blended, the melt is filtered through two stages, metered and extruded to a chilled roller, and the chilled roller cools the melt to obtain a thick sheet to be stretched; after heating in a preheating zone of a synchronous stretching oven, the melt is transversely stretched into a film to ensure that both the rigid COC chain and the flexible PP chain have high molecular chain mobility; after trimming, thickness measurement and corona treatment, the film is rolled up to obtain the biaxially stretched polyolefin film.

Citation Information

Patent Citations

  • Polyolefin membranes and their applications

    CN110546190B

  • Biaxially oriented poly (4-methyl-1-pentene) film and preparation method thereof

    CN112406146A

  • Modified luminescent nano-zinc oxide for photocuring thick coating as well as preparation and application of modified luminescent nano-zinc oxide

    CN116218278A

  • Capacitor containing biaxially stretched polypropylene-cycloolefin polymer film as dielectric, and use of said film

    CN116368175A

  • Anti-ultraviolet ABS (Acrylonitrile Butadiene Styrene) material, preparation method thereof and packaging bottle

    CN117820557A